Scientific Evaluation of Anti-Analgesic and Anti-Inflammatory Efficacy of a Siddha Drug, Sivathai Chooranam (AYUSHDHARA, 2022)
Siddha medicine offers an unceasing development in medical practice for a number of metabolic diseases and lifestyle disorders. The present study was to evaluate the anti analgesic and anti-inflammatory potential of Sivathai chooranam. The animals were divided into 5 groups of 6 animals each {control, standard – Indomethacin (5mg/kg, i.p), sivathai chooranam 0.108mg/kg(po), Sivathai chooranam 0.44 mg/kg(po) and Sivathai chooranam 2.7mg/kg(po). The analgesic activity of the extracts was evaluated using acetic acid induced writhing method and in vitro anti-inflammatory activity was evaluated using HRBC membrane stabilization assay and egg albumin denaturation assay. In acetic acid induced writhing model of analgesia, the number of writhes (in 30 minutes) was highest in control group (49.5±1.707) and lowest in Indomethacin group (26.25±0.629). Analgesic activity in sivathai chooranam at 2.7mg/kg concentration has registered lowest number of writhes (26.25±0.629) compared other drug concentrations tested and it was statistically significant as compared to control group. The concentration of 250µg/ml of Sivathai chooranam has exhibited a maximum percentage of haemolysis (88.24±0.73%) and albumin (protein) denaturation (84.51±0.66%) while the same concentration of standard drug of hydrocortisone represented the haemolysis was 88.94 ± 1.27% and Diclofenac sodium showed the 89.18±0.76 % of protein denaturation. The results of the work indicate that the Siddha medicine, Sivathai chooranam has possessed remarkable anti analgesic and anti inflammatory potential and can be applied as alternative in the treatment of painful conditions and inflammatory complications.